2011
DOI: 10.2741/s147
|View full text |Cite
|
Sign up to set email alerts
|

Periacinar retraction artifact of the prostate

Abstract: Retraction artifacts are well known phenomenon in diagnostic surgical pathology for a long time but they were usually considered as artificially produced tissue alteration. Some recent studies of retraction artifact in different tumors have focused on its diagnostic and/or prognostic role. Their presence in prostatic carcinoma may be used in diagnostic and prognostic purposes. Peritumoral retraction artefacts in prostatic carcinoma are more pronounced and more common around neoplastic glands compared to benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…BCC is microscopically characterized by nests of basaloid cells showing peripheral palisading, surrounded by peritumoral empty spaces that are usually regarded as artifacts due to fixation of specimens. However, there are other suggestions regarding the cause of peritumoral clefting (5,6,18). Acs et al suggested that retraction clefting represents prelymphatic spaces in cases of breast carcinoma (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCC is microscopically characterized by nests of basaloid cells showing peripheral palisading, surrounded by peritumoral empty spaces that are usually regarded as artifacts due to fixation of specimens. However, there are other suggestions regarding the cause of peritumoral clefting (5,6,18). Acs et al suggested that retraction clefting represents prelymphatic spaces in cases of breast carcinoma (8).…”
Section: Discussionmentioning
confidence: 99%
“…Peritumoral clefts (retraction clefting) are empty spaces arround tumor nests that may be seen in different tumor types (5)(6)(7)(8). The exact mechanism of their evolution is still controversial, although the loss of basal epithelial cells, the lower expression of adhesion molecules and the higher expression of proteins involved in extracellular matrix remodeling most probably have a major role.…”
mentioning
confidence: 99%
“…Previously, it was considered merely a laboratory procedure artifact, but lately, there have been some assumptions that peritumoral retractions actually might represent lymphatic spaces. 7 D2-40 (podoplanin antigen) is expressed in lymphatic endothelial cells without reacting with the endothelium of blood capillaries, arteries, or veins in normal and neoplastic tissues, hence allowing lymphatic vessels (LVs) identification and assessment of their density. 8 Therefore, immunohistochemical detection of D2-40 antibody is useful to differentiate actual lymph vessels and lymphatic invasion from periacinar retractions.…”
Section: Introductionmentioning
confidence: 99%
“…The neoplastic cells of prostatic cancer often appear pulled away from the surrounding stroma, leaving empty spaces that completely or partially encircle the acini; these are called retraction clefts or retraction artifacts and were described for the first time in 1960s in autopsy studies by Halpert and co-workers [1,2]. Periacinar retraction clefts in prostatic carcinoma serve as a helpful additional criterion in setting of pathohistological diagnosis, particularly in differentiating it from some benign conditions (atrophy, postatrophic hyperplasia, atypical adenomatous hyperplasia), which may mimic prostatic carcinoma [3][4][5][6][7][8]. They are mostly seen in Gleason grade 3, occasionally appear in grades 2 and 4 but are uncommon in comedo type…”
Section: Introductionmentioning
confidence: 99%